Numerical Modeling of Salinity Intrusion: Case Study from Southern Coastal Aquifer in Sri Lanka - Sarukkalige, Priyantha Ranjan (Institute of Engineers, 2006)
A numerical model based on the freshwater-saltwater sharp interface assumption has been developed and it has been applied to estimate the salinity intrusion in the lower part of the Walawe riverbasin in the southern coastal aquifer, Sri Lanka. Evaluation of the effect of hydro-geological factors on the dynamics of freshwater- saltwater interface has been considered through storage coefficient, porosity and hydraulic conductivity. It concludes that hydraulic conductivity is the main hydro-geological factor affecting the movement of salinity interface. The simulation for groundwater recharge shows that the saltwater intrusion is more sensitive to groundwater recharge than hydro-geological properties. Since storage coefficient and porosity are not much affecting to the change of interface, model was calibrated by adjusting the hydraulic conductivity to match the observed salinity profile in the southern coastal aquifer. The observed long term salinity profile has been compared with the simulation results. It shows that the numerical models can be used to reproduce the salinity profile in the area.